Basic gymnastics exercise intervention to improve some Fundamental movement skills for children with simple movement difficulties - Mohammed, Lubna Kutiba (Dirasat: Educational Sciences, 2020)
Objective: study’s aim was to evaluate the using of basic gymnastics exercises for (6) weeks as an intervention in physical education lecture to improve some Fundamental Movement Skills (FMS) for children with simple movement difficulties. The question of the study was if there is any effect for using basic or simple gymnastics exercises on improving some Fundamental movement skills for children who have simple difficulties in movement...? Design: The study used an experimental method by using two groups a control group and experimental group. Method: The researcher divided the participants into two groups, a control group and experimental group each group include (20 pupils) the total for the research sample were (40 pupils 25 male & 15 female age 6-7 years) (SD=0.28), the intervention was for (6) weeks (18 units) as (20 min) during the PE lecture Results: The results showed there were significant differences between the pre-test and post-test for the experimental group in comparison with the control group, which showed improving, but less than the experimental group. Conclusion: The improvement in performance was a different between skills because of the degree of difficulties as well as the individual differences between the children. Study demonstrated that a gymnastics basic exercises used in the study have accelerated the improvement of some FMS ability for the children with simple movements difficulties.